Morphometric measurements of the caudal cranial nerves in the petroclival region - ÖZDOĞMUŞ, NECMETTİN ÖMER (JOHANN AMBROSIUS BARTH VERLAG MEDIZINVERLAGE HEIDELBERG GMBH, 2007)
Objective: The dural zone of entry or exit of the caudal cranial nerves in the petrodival region does not have a constant localization. The present study aimed to measure the dival length, the distances between cranial nerve dural openings and the distance of cranial nerves from the mid-dival line in 30 human autopsy cases. Material and Methods: Thirty autopsy specimens (8 female, 22 male) from persons aged between 20-76 years (mean age 38.9 years) were studied. Autopsies with intracranial lesions were not included in the study. Results: The average distances between the right and left dural openings of caudal cranial nerves in the petroclival region were as follows (mean sd): trigeminal, 32.17 +/- 5.41 mm; abducent, 20.04 +/- 3.23mm; facial and vestibulocochlear, 50.97 +/- 5.86mm; glossopharyngeal, vagus, accessory, 41.59 +/- 6.46mm and hypoglossal 26.8 +/- 4.33mm. The measurements of the distances of the cranial nerve exits to the mid-clival line showed considerable asymmetries for the left and right trigeminal nerves. Furthermore, the distances between the trigeminal and the abducent nerves on the right and left differed significantly (p < 0.029). The average distance between these two cranial nerves on the left was 8.44 +/- 3.66 mm and on the right was 7.31 +/- 2.41 mm. In addition, the average clival length was 56.96 +/- 5.91 mm (range: 42-71 mm). Conclusions: Most of the surgical procedures performed in this area are to remove tumors which significantly modify the local anatomy. Knowledge of morphometric variations can increase the success of cranial nerve preservation during surgical procedures of the posterior cranial fossa.
Keywords: petroclival region; caudal cranial nerves; clivus; morphometry